TRAINING FOR AN ACCOUNTING CAREER. - Zlatkovich, Charles T. (The Accounting Review, 1958)
In view of the increased attention being paid by the public accounting profession to managerial service engagements one can argue that really the public accountant of tomorrow must be both what he has been in the past plus having a training and viewpoint similar to that of an industrial or managerial accountant. This argument seems to have some validity. If it does, it would follow that the character of the Committee on Professional Education examination ought to continue to change and the pace of change should perhaps be accelerated. The emphasis of some questions could be shifted; the examination could be lengthened to include added subjects; or these subjects could be added and the time allotted to traditional subjects could be reduced. Of course the examination would still place heavy emphasis on traditional subjects such as auditing, commercial law, governmental accounting, taxes, and various financial, cost, and fiduciary accounting material. However, it might also emphasize statistical analysis, economics and economic indicators, managerial policy, controllership, budgetary and cost analysis and the like. It is recognized there could be some legal impediments to such changes, but these are not insurmountable.